Boosting Tourism Village Appeal: Strategies for Effective English Language Content Creation - Fini Asterina Zalukhu; Afore Tahir Harefa; Elwin Piarawan Zebua; Riswan Zega (JELITA, 2024)
This research focuses on improving the promotion of tourism villages using technology to create English-language content. The research uses the Four-D model to create a website-based digital promotional media for Tumori Village in North Sumatra. The website showcases the village's uniqueness, traditional houses, history, etc. The results show that the website can boost tourism promotion globally, contribute to the local economy, and increase village visibility on search engines and social media. The research aims to provide guidance for other villages in developing effective English-language content, enhancing their appeal to international travelers and bringing sustainable benefits to local communities.